Meanings of Mindfulness and Spiritual Awakening: Affliction and Holistic Healing in Contemporary Cairo - El Fakahany, Sohayla (AUC Knowledge Fountain, 2021)
In contemporary Cairo, people turn to various modes of spiritual, alternative, and complementary healing. Some are rooted in formal religious traditions, and others are inspired by a new globalized form of holistic healing such as yoga or meditation. What makes these practices more controversial than spiritual healing practices like el-Zar or el-Hadra is the exchange of money for the promise of healing or foreknowledge. Spiritual healing is often deemed “charlatanistic” by religious exclusivists. This entanglement of the practices with religion creates a threat because it provides an alternative to the modes of religiosity supplied by the main hegemonic Egyptian religious and cultural institutions. There is an interesting cross-pollination between formal religious ideologies about healing and contemporary hybridized modes. A yoga instructor, for instance, might also position the practice of yoga within a religious lifestyle, whether Christian or Muslim. In this research, I explore people’s motivations in choosing or refraining from seeking different kinds of alternative modalities in relation to affliction and healing. The purpose of this project is to answer the question, what factors affect people’s decision of seeking or refraining from pursuing spiritual and alternative practices in contemporary Cairo? Combining preexisting debates and theories with three years of fieldwork and online and on-the-ground ethnographic research, I aim to delve deeper into the reasons and meanings behind people’s choices. These preexisting debates include notions of modernity, mysticism, commodification, careerism, ritual efficacy, performance, governmentality, biopolitics, state-society relations, interpellation, and cultural appropriation. The limitations of these notions and the alike critiques by New Age thinkers are that they do not consider the positive impact these practices might have on people’s wellbeing, discursive formations, and the creation of meaning. I answer the question and analyze these critiques using a multi-sited interpretive reflexive ethnography that was conducted by carrying out participant observation in five wellness places, two from-home practitioners, and five online applications. The interlocutors and interviewees are spiritual healing practitioners and wellness places’ owners. In Egypt, there is a widespread lack of social acceptance that is rooted in financial, religious, and scientific preferences. Locally, this lack of acceptance is also supported by the government, which exerts effort to cancel the existence of unorthodox practices. Globally, there is also a lack of acceptance that is rooted in not only economic and scientific reasons but also cultural ones such as cultural and spiritual appropriation. This piece advocates for having a more holistic approach to wellbeing in conversations about affliction and healing.